Assessing And Mitigation Of Quality Issues Of High-Rise Building Projects In Pakistan - Waheed, Muhammad; Abbas, Mutahir; Hameed Memon, Aftab (Tropical Scientific Journal, 2024)
Objective: Digital innovation service performance indicators are important to the judicial system as it provides system of measurement to assess the efficiency and effectiveness of digital initiatives. These indicators help to identify areas of improvement, optimize processes, and enhance overall service delivery, ensuring that technological advancements align with the system's goals. By tracking key performance indicators, the judicial system can adapt and evolve in response to changing technological landscapes, ultimately enhancing access to justice and the overall functioning of the legal system. Thus, this paper demonstrates a study on ranking the digital innovation service performance indicators for UAE Judicial System. Research Method: The study was conducted using quantitative approach where the data was collected through questionnaire survey on the 332 selected respondents who are employees within the UAE judiciary department and are actively use digital services. Respondents were requested to gauge each of the digital innovation service performance indicators influencing UAE Judicial System using 5-levels of influencing scale. The collected data was analysed using SPSS software to determine the mean score and standard deviation of each of the seven indicators Findings: Based on these values, the highest rank of the indicator that influence that judicial system is “Judicial department make it a priority to be responsive to requests, never too busy to address inquiries” having mean score of 4.291. The outcome of this study able to give awareness to the UAE Judicial System on the importance of digital innovation service performance indicators especially in the speedy responsive to request which is needed in a rapidly changing business environment. Originality: Identification of Digital Innovation Service Performance Indicators Influencing UAE Judicial System.